The Influence of Self-Appreciation, SelfSupervision and Social Supervision on the Appreciation of Akhlaq among Muslim Student - Zakaria, Ros Arniza; Hamzah, Mohd Isa; Abd Razak, Khadijah (International Journal of Psychosocial Rehabilitation, 2020)
One of the government’s aspirations in realising the transformation of the country’s education through the third shift in Malaysia Education Blueprint 2013-2025 is to “Develop Values-driven Malaysians”. This shift can be realised by strengthening Islamic and Moral Education by focusing more on core values and religion. However, akhlaq values that were attempted to be assimilated in the students’ lives through the subject of Islamic Education was insufficient in reducing the student misconduct issue, both in and out of school. This study aims to understand the contributing factors to the appreciation of the akhlaq of Muslim students, including self-appreciation, self-supervision and social supervision. The result of the analysis of previous studies found; (i) self- appreciation factors (understanding & feeling) affect student’s akhlaq appreciation; (ii) the self- supervision factor enhances student moral values and (iii) the social supervision (teachers, parents, friends, community, school, government and law) also influence akhlaq values appreciation. The impacts of this study highlight the importance of enhancing students’ akhlaq values to produce students who are honourable and commendable. Recommendations of quantitative and qualitative follow-up studies should be made to understand this issue better.